2018
DOI: 10.1002/adma.201703748
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Crystalline Black Phosphorus Thin Film on Sapphire

Abstract: Black phosphorus (BP) has recently attracted significant attention due to its exceptional physical properties. Currently, high-quality few-layer and thin-film BP are produced primarily by mechanical exfoliation, limiting their potential in future applications. Here, the synthesis of highly crystalline thin-film BP on 5 mm sapphire substrates by conversion from red to black phosphorus at 700 °C and 1.5 GPa is demonstrated. The synthesized ≈50 nm thick BP thin films are polycrystalline with a crystal domain size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 48 publications
(36 reference statements)
0
92
0
2
Order By: Relevance
“…Top‐down methods such as mechanical cleavage and liquid exfoliation do not seem to work, and bottom‐up methods practiced in conversion from RP to BP may offer a brighter future. For example, Li et al have recently reported the growth of polycrystalline BP on sapphire substrates with large crystal domain size (70 µm) and high mobility at room temperature (160 cm 2 V −1 s −1 ) . However, the current on/off ratio is low (≈9) due to the large thickness (≈50 nm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Top‐down methods such as mechanical cleavage and liquid exfoliation do not seem to work, and bottom‐up methods practiced in conversion from RP to BP may offer a brighter future. For example, Li et al have recently reported the growth of polycrystalline BP on sapphire substrates with large crystal domain size (70 µm) and high mobility at room temperature (160 cm 2 V −1 s −1 ) . However, the current on/off ratio is low (≈9) due to the large thickness (≈50 nm).…”
Section: Discussionmentioning
confidence: 99%
“…The thin‐film BP is continuous up to 600 µm with the crystal domain size up to 70 µm. More importantly, the field‐effect mobility is up to 160 cm 2 V −1 s −1 at room temperature, which is comparable to mechanically exfoliated BP transistors, suggesting a great leap to the realization of large‐scale, high‐quality BP devices for practical applications …”
Section: From Bulk To 2dmentioning
confidence: 93%
“…However, much effort has been paid on solving their stability and improving the device's performance . Additionally, highly crystalline thin‐film BP on 5 mm sapphire substrates has been successfully synthesized . Therefore, BP with a narrow bandgap and high mobility becomes the most promising 2D material that could be applied to sense the IR photons at room temperature.…”
Section: Room‐temperature Ir Photon Detectors Based On Atomic Layer Mmentioning
confidence: 99%
“…Xia's group made progress in 2015, reporting an approach to synthesize millimeter‐sized thick BP films (tens of nanometers in thickness), but with a low sample quality . Later, the same group largely improved the quality of synthesized BP films, with a carrier mobility up to 160 cm 2 (V s) −1 at room temperature . So far, it is still quite challenging to directly synthesize thin‐layer BP with a large area and high quality, requiring further efforts and is long‐waiting for the applications of BP.…”
Section: Introductionmentioning
confidence: 99%